Using “School Films” in Initial Teacher Education: A Reflective Learning Approach - Daniela-Maria Crețu; David Morariu (Educaţia 21)
The use of films in teacher education is both an educational practice and a research direction with significant potential, offering diverse perspectives, numerous benefits, and high relevance for future teachers. This study aims to explore the potential of “school films” in the pedagogical training of pre-service teachers. Our analysis relies on four case studies of films such as Dead Poets Society (Weir, 1989), The Ron Clark Story (Haines, 2006), Freedom Writers (LaGravenese, 2007), Entre les murs [The Class] (Cantet, 2008) that have become classics within the “school films” cinematic sub-genre. The selected films illustrate concepts, theories, or educational practices pertinent to students in the process of their training as future teachers. They also reveal the dynamics of the teacher-student relationship in different contexts, aspects of school life, and the challenges of the teaching profession. Based on these four films, we developed a training project for final-year students in Level I of the Psycho-Pedagogical Training Programme. The project includes activities such as film viewing, debates, and reflective learning strategies. The concept of this project, along with the accompanying tools – primarily worksheets with reflection tasks – can inspire other teacher educators to provide engaging and interesting learning experiences for future educators based on films.